TracLocatEngine: a system for tracking and locating technical personnel using Radio Frequency Identification (RFID) - Olanweraju, Rashidah Funke; Khalifa, Othman Omran; Abdul Latif, Khairun Nisaa’ (2012)

(untitled)
Tracking and locating of objects, human and animals is becoming an important issue in this digital era where computer is virtually embedded in all everyday objects/appliances around us. Radio Frequency Identification (RFID) is one of technologies that have been used in tracking and locating objects, such as animals, goods in shipment and humans. In laboratories, security post, hospitals and aircraft control where technical staffs expertise are highly needed during emergency cases, tracking and locating system is highly required in such situation to located the personnel in charge. An interactive system to track personnel within the land mark of faculty of engineering, International Islamic University Malaysia was developed in this paper. A Graphical User Interface, GUI was designed to displays the details and location of the tracked personnel movement on a map of the faculty. The major advantage of TracLocatEngine is that it improves the accuracy of locating personnel by employing reference tags model.